Answer :

Given,


m2 – 4mn + 4n2


By using the formula (a - b)2 = a2 - 2ab + b2


= m2 - 2×m×2n + (2n)2


= (m – 2n)2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Factorize each ofRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Factorize each ofRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

10p2 +RS Aggarwal - Mathematics

7x2 - RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics